Fano resonances in plasmonic heptamer nano-hole arrays - Hajebifard, Akram; Berini, Pierre (Université d'Ottawa | University of Ottawa, 2017)
The optical properties of gold heptamer nanohole arrays have been investigated theoretically and numerically. This structure support pronounced Fano resonances with high transmittance (~50%) and narrow bandwidths (down to 12 nm). The Fano features arise from the interference between light directly transmitted through the holes, and light indirectly scattered through the excitation of localized surface plasmon polaritons (LSPPs), propagating surface plasmon polaritons (SPPs), or/and waves related to Wood's anomaly (WA). The mechanisms behind the generation of these resonances are revealed by observing near-field distributions, altering the structural parameters and applying the Bloch wave model. Furthermore, it is shown that Fano resonances associated with LSPPs exhibit high surface (2 nm/nm) and bulk sensitivities (400 nm/RIU). However, the highest figure of merit (~24 RIU-1) occurs for a Fano resonance involving a WA and SPP mode.